Bi0.5Na0.5TiO3-based lead-free ceramics with superior energy storage properties at high temperatures. (15th June 2021) - Shi, Peng; Zhu, Xiaopei; Lou, Xiaojie; Yang, Bian; Guo, Xudong; He, Liqiang; Liu, Qida; Yang, Sen; Zhang, Xiaoxiao
Abstract: Dielectric capacitors with high energy storage and dielectric properties at high temperatures have significantly practical application in many fields. Lead-free ceramics of (1- x )(0.65Bi0.5 Na0.5 TiO3 -0.35Bi0.2 Sr0.7 TiO3 )- x BaSnO3 were prepared by a solid-state reaction method. It was found that the 0.8(0.65Bi0.5 Na0.5 TiO3 -0.35Bi0.2 Sr0.7 TiO3 )-0.2BaSnO3 ceramic shows a large recoverable energy storage density ( W r ) of 3.75 J/cm 3 and efficiency ( η ) of 84.8% under 380 kV/cm along with outstanding power density of 38.73 MW/cm 3 under 130 kV/cm at room temperature. Additionally, a high W r of 3.21 J/cm 3 and η of 77% are achieved under a high electric field of 300 kV/cm at 100 °C. When the temperature reaches 140 °C, it still has a high W r of 3.1 J/cm 3 and η of 72%. The outstanding energy storage performance at high temperatures can be explained by the enhancement of breakdown strength and the constructing of polar phase stability caused by the introduction of BaSnO3 .